Bread and Roses Rally, 1980 (1980)
1980 1960-2000 "Bread and Roses Rally, 1980" [T0598.jpg], 1980 Following the election of a Conservative Government in 1979, the TUC launched the Campaign for Economic and Social Advance to publicise its policies on public expenditure and services and to lay out its alternative economic and industrial strategy. In April 1980, the TUC organised a rally in defence of education and the arts at the Theatre Royal, Drury Lane in London entitled Bread and Roses. The rally included not only speeches, but also music, comedy and a variety of other entertainment. A second Bread and Roses event was organised in 1981.